A pilot study of activity of pembrolizumab and low dose chemotherapy in relapsed/refractory T-cell lymphoma: Jordanian experience - Abbasi, Salah; Dwaik, Haytham; Abbasi, Layla; Al Hourani, Huda (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Peripheral T-cell lymphomas (PTCLs) are associated with poor prognosis and limited treatment options in the relapsed/refractory (R/R) setting. Programmed cell death-1 and ligand-1 (PD-1 and PD-L1) are frequently expressed in T-cell Lymphoma. It provides a rationale for using immune checkpoint inhibitors (ICIs) to manage PTCLs. Many studies in solid tumors showed higher efficacy of ICIs when used in combination with chemotherapy. Methods: A study of 11 patients with R/R PTCLs was conducted retrospectively. They were treated at two Jordanian hospitals with Pembrolizumab, Vincristine, and Cyclophosphamide every three weeks. Results: The overall response rate (ORR) was 63%, with three complete responses (CR) and four partial responses (PR). The median progression-free survival (PFS) was 4.0 months (95% CI: 1.7 to 11.4), and the median overall survival (OS) was 17.0 months (95% CI: 0.7 to 33.2). Conclusions: Pembrolizumab and low-dose chemotherapy demonstrated promising activity in R/R PTCL, with high response rates. Furthermore, extensive studies are needed to define the role of such an approach.